Moderating Effects of Exercise Duration and Intensity in Neuromuscular vs. Endurance Exercise Interventions for the Treatment of Depression: A Meta-Analytical Review - Nebiker, Lukas; Lichtenstein, Eric; Minghetti, Alice; Zahner, Lukas; Gerber, Markus; Faude, Oliver; Donath, Lars (Frontiers in Psychiatry, 2018)
Background: Exercise training is a beneficial treatment strategy for depression. Previous meta-analytical reviews mainly examined the effect of aerobic exercise on depressive symptoms neglecting comparisons with neuromuscular training and meta-regression considering relevant exercise training prescriptors such as exercise duration, intensity, number of exercise sessions (volume) and frequency. Methods: A structured literature search was conducted in biomedical and psychological databases and study selection was conducted following the PICOS approach. (Randomized) controlled trials that compared supervised neuromuscular or endurance exercise interventions with an inactive control group (CON) in clinically depressed in- or out-patients over 18 years were included. Eligibility and study quality were evaluated by two independent researchers. Standardized mean differences (SMD) for the reduction of depressive symptoms, measured with different evaluation scales (e.g., BDI, HAM-D, PHQ-9, HRSD, MADRS, GDS) were calculated with the adjusted Hedges'g equation as main outcome for the comparison of endurance and neuromuscular exercise interventions vs. CON. Statistical analyses were conducted using a random effects inverse-variance model. Multivariate meta-regression analysis was performed in order to examine the modulating effects of exercise training prescriptors. Results: Twenty seven trials with 1,452 clinically depressed adults were included. 20 out of 27 included trials reached a PEDro score of at least 6, representing high-quality. Irrespective of the exercise mode and study quality, large effects in favor of exercise compared to the control condition were found. Compared to CON, sensitivity analyses revealed a moderate to large effect in favor of endurance exercise [SMD: −0.79 (90% CI: −1.10, −0.48); p < 0.00001, I2 = 84%] and a large effect size in favor of neuromuscular exercise [SMD: −1.14 (90 CI: −1.50, −0.78); p < 0.00001, I2 = 80%]. These effects decreased to moderate for endurance and remained large for neuromuscular trials when considering studies of high quality, indicating a significant difference (p = 0.04). Multivariate meta- regression revealed that exercise duration in endurance trials and exercise intensity in neuromuscular trials had a significantly moderating effect. Conclusions: Strong neuromuscular exercise interventions can be slightly more effective than endurance exercise interventions. Interestingly, exercise duration and exercise intensity moderated the effect size meaningfully. This result might be used on exercise in depression to increase efficacy.